2014
DOI: 10.1007/s11270-014-2040-8
|View full text |Cite
|
Sign up to set email alerts
|

Alkylphenols in Surface Sediments of the Gulf of Gdansk (Baltic Sea)

Abstract: The widespread use of alkylphenols in European industry has led to their presence in the environment and the living organisms of the Baltic Sea. The present study (2011–2012) was designed to determine the concentrations of alkylphenols, 4-nonylphenol (NP) and 4-tert-octylphenol (OP), in surface sediments of the Gulf of Gdansk, a section of the Baltic that lies in close proximity to industrial and agricultural areas and borders with an agglomeration of nearly one million inhabitants. It is also where the Vistul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…As was the case with NP, the concentrations of OP were much higher in the sediments of Southeast Asia than in the Gulf of Gdansk; while in present study NP were found significantly higher as compare to OP. (Koniecko et al 2014). Estrone was detected in all surface sediment samples; and its concentration varies from 6.5 to 16.3 μg kg −1 with average value of 11.8 μg kg −1 .…”
Section: Distribution Of Other Edcsmentioning
confidence: 89%
“…As was the case with NP, the concentrations of OP were much higher in the sediments of Southeast Asia than in the Gulf of Gdansk; while in present study NP were found significantly higher as compare to OP. (Koniecko et al 2014). Estrone was detected in all surface sediment samples; and its concentration varies from 6.5 to 16.3 μg kg −1 with average value of 11.8 μg kg −1 .…”
Section: Distribution Of Other Edcsmentioning
confidence: 89%
“…The presence of NP in freshwater sediments was primarily ascribed to domestic and industrial wastes and to a lesser extent by agricultural activities (pesticide applications, sludge amendment, and irrigation with wastewater). Koniecko et al ( 2014 ) recognized the rivers and surface runoff as the main sources of NP in coastal sediments of the Gulf of Gdansk; however, they also indicated the possibility of atmospheric transportation of black carbon originating from combustion processes on land along with adsorbed alkylphenols. In Central Europe, Micic and Hofmann ( 2009 ) detected concentrations of NP between <0.02 and 2.83 mg/kg d.w. in sediment samples collected along the Danube River; important point sources were industrial sites, especially oil refineries, and drains of untreated wastewater.…”
Section: Nonylphenol (Np)mentioning
confidence: 99%
“…Sediments that form in the outlet parts of rivers become a ''repository'' of these compounds and they are likely to be transported further, both near the bottom into the accumulation zone and into the water column as a result of windinduced mixing. At the outlets of the Kacza and Gizdepka rivers, sandy and even pebbly sediments are formed, which possess very low sorptive properties (Koniecko et al, 2014). Based on the offshore stations, a clearly defined cluster was formed with higher endocrine compound concentrations in the sub-surface water.…”
mentioning
confidence: 99%